Do Public Sector Employment Reductions Promote Informality? - Antonis Adam; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using information from all IMF conditionality programs from 1990 to 2018, we implement a dynamic Augmented Inverse Probability Weighting Regression Adjustment approach to examine the effects of programs, including public sector dismissals, on the size of the shadow economy. The estimated effect five years after the policy intervention indicates an increase in the share of the shadow economy to GDP by about 1.3 percentage points. More importantly, this change involves a sizable reallocation of private economic activity from its formal to its informal part, i.e., the size of the formal private sector relative to the size of the informal sector decreases by seven percentage points. We interpret these findings through the lens of a two-sector model in which there is interdependence between worker incomes and the allocation of product demand across the formal and informal sectors.
Keywords: O17; J45; 330; shadow economy; public sector employment; IMF programs; informality